It´s not all about guns and gangs: role overload as a source of stress for male and female police officers - Duxbury, Linda (Policing and society, 2018)
This research uses male (n = 1169) and female (n = 300) samples of police officers and multivariate techniques to test a model which hypothesises: (1) work-role overload and family-role overload will predict stress, (2) objective (i.e. hours employed) and subjective (i.e. non-supportive culture, pressures to perform work outside their mandate, competing demands) work demands will predict work-role overload, (3) objective (i.e. dependent care hours) family demands will predict family-role overload and (4) gender differences across all paths. Results showed the relationship between work-role overload and stress was stronger for male police officers, whereas the relationship between family-role overload and stress was stronger for female police officers. Hours employed, performing work outside one’s mandate, and perceptions of the work culture as non-supportive were stronger predictors of work-role overload for the female officers in our sample than for their male counterparts. The path between hours in dependent care hours and family-role overload was also stronger for female than male police officers. Competing work demands, on the other hand, was a stronger predictor of work- role overload for male than female police officers.